Pengembangan Media Pembelajaran Membaca Teks Anekdot Berbasis Google Site pada Siswa Kelas X - Nasrullah, Mohamad Irvan; Eriyani, Reni Nur; Murtadho, Fathiaty (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2024)
This research aims to develop learning media for reading anecdotal texts based on Google Site. Based on analysis data, learning media was developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model in Research and Development research. Development begins with analysis which includes analysis of the curriculum, teaching materials, student situations and needs, and interviews with Indonesian language teachers. The results of the analysis of the situation and student needs show that the majority of students use textbooks as a learning resource and students also expect interactive learning to help students understand Indonesian language material and also increase interest in learning. Based on the results of the analysis, a Google Site media research design was developed consisting of (1) home page, (2) competency button, (3) material button, (4) forum button, and (5) practice questions button, and (6) references . Based on the design results, a Google Site-based learning media development was prepared. Based on the results of development, the product was implemented in the form of product confirmation to teachers with